Fatores que influenciam o desempenho docente da pós-graduação stricto sensu na área de engenharias III no Brasil - Teixeira, Tatiane (2019)
This dissertation aims to relate the factors listed in the literature to the perception of professors inserted in the graduate with grade 6 and 7 of Capes, in the engineering III area in Brazil. The methodology is divided in two parts, the former treating the literature review construction method, and the last presents the research application and data analysis method. The literature review is the research of studies in the Scopus and Web of Science databases between 2008 and 2018, using the keywords: performance, professor and graduate, which contributed to map 79 factors distributed in eight categories named as: (i) pedagogical, scientific and didactical performance, (ii) professor training, (iii) teaching methods, (iv) pedagogical update, (v) health, (vi) knowledge management, (vii) students’ perspective and (viii) scientific production. Among the 32% of the studies with factors associated to the scientific production, 16% studied the professor training, 14% are in the pedagogical, scientific and didactical performance category and other 14% are in the teaching methods one. The research application was made through a questionnaire sent to 235 professors from ten universities: ITA (39 professors), UFRJ (12 professors), PUC/PR (12 professors), UFSC (43 professors), UFRGS (30 professors), UFPE (13 professors), UFRGS (16 professors), PUC/RIO (18 professors), UFU (27 professors) and UFRJ (26 professors). 61 responses were obtained, which are about 25,96% of the questionnaires sent. The data analysis was made through the Statistical Package for the Social Sciences SPSS software, version 23, contemplating attendance analysis, T test independent through two groups (men and women), studies of correlation and qualitative analysis. The results showed that in the professors’ perception, there are 96 influential factors on graduate professors’ performance. These factors were placed in 24 categories, in which 6 of them are similar to the literature: scientific productions, professor training, teaching methods, students’ perspective, health, and knowledge management. The professors also mentioned other 18 categories, which there are not in the literature: program evaluation, ability to attract students, city structure, professor reception to the program, industry collaboration, national scenario, feedback, overwork, students’ quality, payment, research environment, international experiences, resources availability, challenges/uniqueness, professional profile, work satisfaction, administrative support to professors and teamwork. The factors that professors more cited were placed in the categories: personal profile (27,9%), resources availability (24,60%) and scientific production (14,8%).